Complex MitraClip procedure for a complex patient: the challenge of commissural flail. Issue 8 (August 2019) - De Luca, Antonio; Caiffa, Thomas; Albani, Stefano; Vitrella, Giancarlo; Rakar, Serena; Perkan, Andrea; Pinamonti, Bruno; Sinagra, Gianfranco
Abstract : Supplemental Digital Content is available in the text